Historia del pensamiento político griego : teoría y praxis - Barceló, Pedro, 1950-; Hernández de la Fuente, David A. (Colección Estructuras y procesos. Serie Ciencias sociales., 2014)
The object of this book is to analyze the genesis and development of political theory and praxis in ancient Greece, from the archaic period to the beginning of the Hellenistic era.